2005
DOI: 10.3794/ijme.43.124
|View full text |Cite
|
Sign up to set email alerts
|

Using case studies in managment education: the student perspective

Abstract: U Us si in ng g c ca as se e s st tu ud di ie es s i in n m ma an na ag ge em me en nt t e ed du uc ca at ti io on n: : t th he e s st tu ud de en nt t p pe er rs sp pe ec ct ti iv ve e Ross Brennan and S. Jaseem Ahmad, Middlesex University Business School AbstractCase studies are widely used in management education. Most of the literature discussing the case study method has reflected the perspective of the teacher, implying a teacher-centred view of the case study as a learning strategy. Little is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…To increase engagement and interest, academics have focused on providing more stimulating and student-orientated case material with some success (O'Cinneide, 2006). However, in their study of the student experience of case use, Brennan & Ahmad (2005) found a substantial minority (30%) of their sample of Marketing and Management students had less than favourable attitudes towards pedagogy based on text based case studies. Our own teaching experiences in the increasingly common "massified" higher educational context concur with this finding.…”
Section: Engagementmentioning
confidence: 95%
See 2 more Smart Citations
“…To increase engagement and interest, academics have focused on providing more stimulating and student-orientated case material with some success (O'Cinneide, 2006). However, in their study of the student experience of case use, Brennan & Ahmad (2005) found a substantial minority (30%) of their sample of Marketing and Management students had less than favourable attitudes towards pedagogy based on text based case studies. Our own teaching experiences in the increasingly common "massified" higher educational context concur with this finding.…”
Section: Engagementmentioning
confidence: 95%
“…Many authors (Kreber, 2001;Rippin, Booth, Bowie & Jordan, 2002;Brennan & Ahmad, 2005) have outlined the history of using case studies in business and management education over the last century. In fields such as Business and Management, it is often the primary mode of instruction (Alexander, O'Neill, Snyder & Townsend, 1986).…”
Section: Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst reservations have been expressed, generally speaking students on marketing and strategy courses, when you ask them, tend towards the opinion that the use of case studies helps them to learn valuable analytical and communications skills, and to bring the real world of business into the classroom. There is some evidence that there are important differences between different categories of student in terms of attitudes towards case studies-for example, between students with different types of entry qualifications, between more and less mature students, and between students from different ethnic backgrounds (Brennan & Ahmad 2005). But in general case studies are a learning approach that is fairly well-liked by students, and one which they think is effective.…”
Section: The Tactics Of Using Cases In Marketing Educationmentioning
confidence: 99%
“…Tinha sido uma longa semana, e parecia que seria um longo final de semana também, porque precisava preparar a reunião que teria na segunda-feira sobre os níveis mundiais de estoques da impressora Deskjet". O estudante precisa estar bastante envolvido com a história apresentada para que de fato participe da discussão (Christensen, 1991;Levin, 1995), haja vista que, para que o método do caso seja efetivo, a participação dos alunos é fundamental (Bontis et al, 2009;Brennan & Ahmad, 2005;Siciliano & Mcaleer, 1997). Esse envolvimento só é obtido se o caso retratar problemas do dia a dia dos alunos (Corey, 1998), e se houver identificação com o protagonista do caso, aquele que deve tomar as decisões (Franke, 2011;Sebenius, 2011).…”
Section: Desenvolvimento E Redação De Casos Para Ensinounclassified